Articulation of Islam: President Joko Widodo’s Foreign Policy 2014-2019 - Achmad Ubaedillah; Muhammad Ali; Bimo Arfino (Jurnal Hubungan Internasional, 2023)
The paper discusses how President Joko Widodo articulated Islamic identity in his Foreign Policy during his first period of Presidency, 2014-2019. Through Constructivism approach and the concept of identity operated eclectically, the study finds that the factor of Islamic identity, to some extent, has contributed to the formation and implementation of foreign policy during this period. The Islamic identity can be approved by analytical descriptive explanation as it considered as the common measurement in international relation discipline, which is the platform and foreign policy orientation of Jokowi, in addition to his consistent diplomacy for Muslim world like Saudi Arabia-Iran conflict, Rohingya crisis, Afghanistan, and the existing two President Special Envoys for Middle East and OIC and for Cultural Cooperation and Interfaith Dialogues. This study shows that Jokowi was anti-Islam as accused by many during this period. Theoretically, the constructivism approach offers a new perspective on understanding the relationship of Islam and state in contemporary Indonesia.